Current status of the anti-rabies act of 2007 through the lens of key local government officials in the province of Pampanga, Philippines a qualitative study - Lacson, Mona Lisa B. (The Philippine Journal of Veterinary Medicine, 2022)
In this study, the status of the implementation of the Anti-Rabies Act of 2007 as perceived by key LGU officials in the different municipalities of the province of Pampanga was determined. Qualitative research through a small group discussion was conducted among key city/municipality officials. All interviews, with the consent of the participants, were audio-recorded, transcribed, and collated. All relevant information related to the implementation of the Anti-Rabies Act of 2007 was consolidated and interpreted. Based on this interview, the implementation of the Anti-Rabies Act of 2007 in terms of compliance with the provisions in the law and the different animal rabies-related programs implemented in the city/municipality were also identified. In addition, the perceived needs of the participating officials to effectively control and eliminate animal rabies in the city/municipality were identified. Based on the results, the province of Pampanga has a long way to go with regards to animal rabies elimination. The majority of the LGUs in the province still need improvement in the implementation of the Anti-Rabies Act.